The book thief - Zusak, Markus (New York Alfred A. Knopf, 2007)
Trying to make sense of the horrors of World War II, Death relates the story of Liesel--a young German girl whose book-stealing and story-telling talents help sustain her family and the Jewish man they are hiding, as well as their neighbors. Includes readers' guide
Michael Printz Award honor book, 2007
1
Keywords: Books and reading -- Fiction; Death -- Fiction; Jews -- Germany -- History -- 1933-1945 -- Fiction; Storytelling -- Fiction; World War, 1939-1945 -- Jews -- Rescue -- Fiction; Germany -- History -- 1933-1945 -- Juvenile fiction; Germany -- History -- 1933-1945 -- Fiction